Beyond `crude pragmatism` in sports coaching: Insights from C.S. Peirce, William James and John Dewey - Jenkins, S. P. R. (International Journal of Sports Science & Coaching, 2017)
There is a lack of clarity in the sports coaching literature about philosophical pragmatism, but the work of Classical Pragmatists such as C.S. Peirce, William James and John Dewey is worthy of attention by both practitioners and researchers. This stimulus article is divided into four sections: Pragmatic Temperament, which includes a discussion of how English Premier League soccer manager Arsène Wenger might be regarded as pragmatic; Communities of Inquiry, which makes reference to a philosophy group at English Premiership rugby union club Saracens; Mixed Methods Research, which examines the use of abduction, deduction and induction in research; and Reflection, which shows how Schön`s reflective practice is a reworking of Dewey`s theory of inquiry. ABSTRACT FROM AUTHOR